Flipped classroom with collaborative learning approach in enhancing writing skills of Indonesian university students - Kheryadi Kheryadi; Muchlas Suseno; Ninuk Lustyantie (International Journal of Evaluation and Research in Education (IJERE), 2024)
The intention of this study was to examine how a flipped classroom with a collaborative learning approach improved the writing skills of Indonesian higher education students. To achieve the study’s aim of 48 Indonesian higher education participants, the Oxford Quick Placement Test (OQPT) was employed. They were divided into two groups: experiment and control. Following that, as a pre-test, both groups were given a written exam. The experimental class (EC) was then positioned in a flipped classroom. Students were permitted to bring smartphones to class and utilize them while learning, and the flipped classroom was equipped with an internet connection, a laptop, and a projector. The control class (CC) got standard classroom instruction. This strategy was employed until the very last session. The experimental group outperformed the control group on the post-test, according to the results of the independent samples t-test and one-way analysis of covariance (ANCOVA). Furthermore, the results revealed a significant difference in post-test performance between the EC and CC.